2020
DOI: 10.1097/01.asw.0000694156.62834.8b
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography as a Diagnostic Tool for Peripheral Artery Disease

Abstract: OBJECTIVE The prevalence of peripheral arterial disease (PAD) is increasing worldwide. The ankle-brachial index (ABI) is considered the criterion standard of noninvasive screening, but it does have limitations. The present study aimed to clarify the clinical diagnostic potential of infrared thermography (IRT) compared with conventional noninvasive measurements for PAD. METHODS Patients were divided into two groups: the healthy control group (n = 93) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
1
17
1
1
Order By: Relevance
“…As reported in our previous studies, we have investigated the use of IRT as a diagnostic tool among PAD patients and patients with diabetes. 21,22 Our outcome here in the present study strengthens these earlier findings and suggests that one of the most effective ways to use IRT is to use it as a follow-up tool among people with diabetes. It is also a valuable tool in the follow-up of PAD patients and patients with diabetes, who have had previous revascularization.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As reported in our previous studies, we have investigated the use of IRT as a diagnostic tool among PAD patients and patients with diabetes. 21,22 Our outcome here in the present study strengthens these earlier findings and suggests that one of the most effective ways to use IRT is to use it as a follow-up tool among people with diabetes. It is also a valuable tool in the follow-up of PAD patients and patients with diabetes, who have had previous revascularization.…”
Section: Discussionsupporting
confidence: 88%
“…IRT can be a revealing tool, especially among people with diabetes, and provides valuable information among PAD patients; however, temperature variation is not as broad as among patients with diabetes. 21,22 Surgical or endovascular procedures for stenotic arteries of leg peripheral circulation are intended to lead to sufficient blood flow. The purpose of this study was with a simple clinical setting to compare skin temperature changes in the feet before and after revascularization and to identify possible correlation between ABI and TP values and foot skin temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, 11.4% of thermal patterns from different healthy participants were asymmetric. Asymmetric or low temperature on one side of the foot is usually an indicator of peripheral artery disease in people with diabetes (36). However, it was found in healthy participants in this study, which suggested that assessment based on a single thermal image is insufficient to judge the risk of DFUs; thus, assessment of plantar thermal images on a regular basis is more reliable.…”
Section: Discussioncontrasting
confidence: 64%
“…The majority of their PAD sample was composed of claudicants, and the authors concluded that in these patients, the temperatures obtained were higher than those obtained from healthy control controls with normal ABI. According to them, this finding was attributed to vasodilation of small arterial vessels as a compensatory response to the overall reduction in blood flow [ 19 ]. This finding was not confirmed in our study and might be because of the small number of claudicants in our series.…”
Section: Discussionmentioning
confidence: 99%